The development of the institution of military quartering as a public burdens for the defence of the State Polish soil until 1939 - Konarski, Marcin (Prawo Kanoniczne, 2021)
Among the many public burdens of a personal or financial nature for the defence of the State that existed in the distant past, one of the oldest and most burdensome is the obligation to provide quarters for the army. This burden was characterised by the fact that the inhabitants of villages, and then of settlements and towns, were forced to provide quarters for the army, As a rule, their owners receiving a certain amount of remuneration, which, however, was often disproportionately low compared to the damage caused by the army to the property providing the quarters. Therefore, the biggest problem with this institution was, for a long time, the one relating to the numerous robberies and destruction carried out by military units. This article is a synthetic analysis of the development of the institution of military quartering on Polish soil from the earliest times, through the period of partitions and the rebith of Poland in the interwar period, to the outbreak of World War II.